TCF7L2 (Transcription Factor 7-Like 2) Regulation of GATA6 (GATA-Binding Protein 6)-Dependent and -Independent Vascular Smooth Muscle Cell Plasticity and Intimal Hyperplasia. Issue 2 (February 2019) - Srivastava, Roshni; Rolyan, Harshvardhan; Xie, Yi; Li, Na; Bhat, Neha; Hong, Lingjuan; Esteghamat, Fatemehsadat; Adeniran, Adebowale; Geirsson, Arnar; Zhang, Jiasheng; Ge, Guanghao; Nobrega, Marcelo; et al.
Abstract : Objective—: TCF7L2 (transcription factor 7-like 2) is a Wnt-regulated transcription factor that maintains stemness and promotes proliferation in embryonic tissues and adult stem cells. Mice with a coronary artery disease–linked mutation in Wnt-coreceptor LRP6 (LDL receptor-related protein 6) exhibit vascular smooth muscle cell dedifferentiation and obstructive coronary artery disease, which are paradoxically associated with reduced TCF7L2 expression. We conducted a comprehensive study to explore the role of TCF7L2 in vascular smooth muscle cell differentiation and protection against intimal hyperplasia. Approach and Results—: Using multiple mouse models, we demonstrate here that TCF7L2 promotes differentiation and inhibits proliferation of vascular smooth muscle cells. TCF7L2 accomplishes these effects by stabilization of GATA6 (GATA-binding protein 6) and upregulation of SM-MHC (smooth muscle cell myosin heavy chain) and cell cycle inhibitors. Accordingly, TCF7L2 haploinsufficient mice exhibited increased susceptibility to injury-induced hyperplasia, while mice overexpressing TCF7L2 were protected against injury-induced intimal hyperplasia compared with wild-type littermates. Consequently, the overexpression of TCF7L2 in LRP6 mutant mice rescued the injury-induced intimal hyperplasia. Conclusions—: Our novel findings imply cell type-specific functional role of TCF7L2 and provide critical insight into mechanisms underlying the pathogenesis of intimal hyperplasia. Abstract : Supplemental Digital Content is available in the text.